Answer:
The equation ax²+bx+c has no solutions
Step-by-step explanation:
I am assuming that the equation is ax²+bx+c = 0. Lets call r₁ and r₂ the roots, then
[tex] ax^2+bx+c = a(x-r_1)(x-r_2) [/tex]
The roots r₁ and r₂ can be computed with the quadratic formula
[tex]r_1, r_2 = \frac{-b^+_-\sqrt{b^2-4ac}}{2a}[/tex]
The discriminant is zero, therefore b²-4ac = 0, and as a result
[tex]r_1, r_2 = \frac{-b}{2a}[/tex]
Since both roots are equal, then we can call them r, with r equal to -b/2a. Replacing this in the factorization gives us as a result
[tex] ax^2+bx+c = a(x-r)² [/tex]
Note that a is positive and (x-r)² is zero at least, this means that the product is equal or greater than zero for every value of x. We conclude that the equation a x² + bx + c < 0 has no solutions.